2020
DOI: 10.1021/acsami.0c11531
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of PtNi Nanowire Array Electrodes toward Oxygen Reduction Reaction by Half-Cell Measurement and PEMFC Test

Abstract: A clear understanding of catalytic activity enhancement mechanisms in fuel cell operation is necessary for a full degree translation of the latest generation of non-Pt/C fuel cell electrocatalysts into high performance electrodes in proton exchange membrane fuel cells (PEMFCs). In this work, PtNi nanowire (NW) array gas diffusion electrodes (GDEs) are fabricated from Pt nanowire arrays with Ni impregnation. A 2.84-fold improvement in the ORR catalytic activity is observed for the PtNi NW array GDE (cf. the Pt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…14,42,48,49 However, further approaches to enhance the catalytic activity of the 1D Pt nanostructures through alloying remain a challenge because of the stability issue of the alloyed metals. 8 Our previous studies demonstrated a more pronounced degradation mechanism of the bimetallic 1D Pt nanostructures hybridized with Ag and Ni, 24,50 induced by the atomic segregation and susceptibility of the transition metals to oxidation in electrochemical reaction under acidic conditions. Hence, the bimetallic 1D nanostructures showed an about 10% larger ECSA loss aer the ADT than their monometallic counterpart.…”
Section: Resultsmentioning
confidence: 97%
“…14,42,48,49 However, further approaches to enhance the catalytic activity of the 1D Pt nanostructures through alloying remain a challenge because of the stability issue of the alloyed metals. 8 Our previous studies demonstrated a more pronounced degradation mechanism of the bimetallic 1D Pt nanostructures hybridized with Ag and Ni, 24,50 induced by the atomic segregation and susceptibility of the transition metals to oxidation in electrochemical reaction under acidic conditions. Hence, the bimetallic 1D nanostructures showed an about 10% larger ECSA loss aer the ADT than their monometallic counterpart.…”
Section: Resultsmentioning
confidence: 97%
“…The following proposals are urgently to be motivated: (1) RHE should be used as RE as far as possible, and if other REs are adopted, their details of potential conversion vs. RHE should be illustrated, and there is no need to conduct iR-drop correction if Luggin capillary is placed correctly in TF-RDE test; (2) To simulate the standard MEA polarization protocol proposed by DOE and narrow the gap of ORR activities obtained via TF-RDE and MEA, reciprocating LSV/SCV should be performed to characterize the ORR performances of PGMs; (3) Connotations like M A and S A should be defined precisely, and K-L equation as well as the selection of j L should be emphasized; (4) The details of calculation processes, such as m Pt , j A , j L , and ECSA et al., should be listed in article or supplemental information for the better readability for readers. Furthermore, considering the limited mass transport in TF-RDE and its discrepancy in test conditions with respect to MEA, whose fabrication process is very much an art, floating electrode ( Lin et al., 2020 ; Zalitis et al., 2013 ) and gas diffusion electrode ( Inaba et al., 2018 ; Mardle et al., 2020 ; Roudbari et al., 2020 ) techniques have been proposed in recent years and are under rapid development to bridge the activity gap between TF-RDE and MEA while maintaining its simplicity, convenience, and controllability.…”
Section: Discussionmentioning
confidence: 99%
“…For all ex situ measurements, a half cell arrangement was made using a FlexCell (PTFE) (Gaskatel) as previously described [34]. The cell consists of a gas compartment in which a rectangular GDE (5 × 3 cm 2 ) was held by O-rings of 3 cm 2 active area.…”
Section: Ex Situ Gde Measurementsmentioning
confidence: 99%